Peningkatan Kemampuan Masyarakat Desa Tirtonirmolo dalam Pengolahan Limbah Peternakan Menjadi Pupuk Organik - Maryudi, Maryudi; Aktawan, Agus (Penerbit Goodwood, 2024)
Purpose: Indonesia is an agricultural country and many people own livestock. Livestock produces solid manure waste that can be converted into organic fertilizers. Livestock waste has not been treated properly, so community service was conducted to overcome this issue. Community service activities were conducted in the form of training on livestock waste processing into solid organic fertilizer and liquid organic fertilizer for members of The Community Self-Reliance Agency (BKM)